MENTAL HEALTH EDUCATION FOR TEENS IN TPQ DARUSSALAM SIDOARJO - Faida Annisa; Muniroh (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Mental health is not only the absence of mental disorders, but also shows the individual's ability to carry out roles in life in a balanced and harmonious manner with other people. The issue of mental health problems occurs in adolescents that their lives currently revolve around social media which have an impact on their mental health. Education program about mental health for teens is a form of community service in order to prevent mental health problems in adolescents. Implementation of the mental health education for teens took place on January 9, 2023 at TPQ Darussalam Sidoarjo. The target of this activity was students aged 12-15 years. There was a process of preparing the activity for approximately 4 weeks by starting the permits from related parties. As a form of evaluation, the activity was attended by 23 students and they took part in the activity cooperative and enthusiastically. They were able to describe the criteria of mental health and how to maintain it.